Association between the inflammatory burden index and rheumatoid arthritis and its all-cause mortality: data from NHANES 1999–2018 - Zhai, Jiali; Yuan, Bo; Liu, Tiebing; Mo, Linfei; Xie, Yajie; Zhao, Yi; Cao, Shuai; Meng, Liesu (Frontiers in Medicine, 2024)
Background and aims Rheumatoid arthritis (RA) is a prevalent chronic autoimmune disease characterized by chronic inflammation. The Inflammatory Burden Index (IBI) is a newly proposed comprehensive inflammation index used to assess systemic inflammation. The relationship between IBI and RA, as well as its all-cause mortality, remains unclear. The objective of this study was to examine the correlation between IBI and RA and to analyze the association between IBI and all-cause mortality in RA. Methods The study comprehensively analyzes adult data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999 to 2018. The participants’ IBI was calculated using the formula IBI = CRP * neutrophils/lymphocytes. Three models were constructed to investigate the relationship between IBI and the prevalence of RA. Nonlinear relationships were determined using restricted cubic spline curves. Stratified analyses and interaction tests were used to explore the relationship between RA and IBI in different subgroups. The same data analyses were applied to investigate the association between IBI and RA all-cause mortality. Results The data analyses revealed a stable positive and nonlinear correlation between IBI and the risk of RA, as well as a positive, nonlinear, J-shaped association between IBI and RA all-cause mortality. The correlation and association were consistent across most subgroups, and multiple covariates had no effect on the results. No significant effect of multiple covariates on the association was found through interaction tests. Conclusion Our study has demonstrated a positive correlation between the prevalence of RA and all-cause mortality with the IBI index. This suggests that lower levels of inflammation in the body are associated with a reduced risk of RA prevalence and all-cause mortality. Further prospective studies are required to explore the mechanisms involved.